Análise do uso de controles e gestão financeira em propriedades rurais produtoras de grãos da Região Oeste do Paraná - Souza, Leonor Venson de (2016)
Taking into account the economical aspects in the agricultural area in Brazil from the last decades and also the performance from the grains production broadcasted by official records, this agricultural sector has been drawing attention to many researches and showing a total lack of proper financial management.Given the importance of financial management and controls and also by analyzing the situation on the country land where the rural producers have been dedicating more time to things related to production than to financial management which demands more assertive decisions that are essential to the maintenance of those rural enterprises and also considering the lack of proper management of the agricultural areas, the objective of this study was to analyze the use of controls and financial management in grain production rural areas from the west of Parana State in Brazil. We have divided a study in two different steps; first we have made an structured survey in 80 rural producers in the West of Parana, from October 2015 to February 2016, about the use of controls and financial management done by the producers. On the second step, we have shown to 10 of those who participated on the survey a proposal of a system of information on cash flow. Inspired by an accounting model which was adapted for this system and it was applied to 10 of those properties between the months of February and July in 2016. The study, that was descriptive and qualitative, was based on literature review and on periodicals identified in researches and surveys based on specialized bibliographies and in libraries. The results from the first step showed an absence of controls and financial management in the surveyed rural properties , regardless of the technological information and communication advancements, many decisions are still based in empirical knowledge and the systems of financial managements are rarely used and restrict. The use of a system of information of cash flow in the rural activity, on the second step, pointed out innumerous benefits such as control of expenses and the analysis of results, among others, was only possible to be estimated by the rural manager. Considering the advancements in the use of technology of information and better access to the internet in the country, new researches can contribute to foster management techniques in the rural field such as distance learning and the development of tools that can be more proper to the profile of the rural producers